Reprogramming Mind for Business Success - Zamfir Cristina Mihaela (Ovidius University Annals: Economic Sciences Series, 2018)
In the context of business, an opportunity for guaranteed success is to reprogram our mind, diffuse disputes, zap away limiting habits and beliefs and step into more positive feelings. Firstly, the paper attempts to demonstrate that it is absolutely necessary for our actions to have a purpose in order to bring about self-development and a relationship of rapport. Secondly, the article helps us to effectively consider the powerful role of finding alternatives and responses to people and situations in today’s workplace. The use of neuro-linguistic programming (NLP) tools and techniques allows us to enrich our personal map in the pursuit of business excellence. The results of the research show that generating new and empowering thinking styles are able to support us in achieving positive outcomes.